New Avenues of Logistics and Transportation Laws in Supply Chain Management: Issues and Challenges - Hamzah Hamzah (International Journal of Supply Chain Management, 2018)
While dealing with trade, either at domestic or international market, legal considerations involve in logistics and transportation in supply chain has played their significant role. The field of laws and regulations has been emerged over time with some serious issues at global market. Present study has reviewed the opportunities with the issues and trends involved in logistics and transportation. For this purpose, a comprehensive review is developed with some meaningful suggestions to develop a comprehensive understanding as well. In this regard, the field of Operational research (OR), its historical trends, legal issues for the transportation of goods, international commercial terms, and finally the shipped documents are very much important. Although the complexity level has been increased while dealing with the legal formalities, the compliance of shipped documents can provide the firm with better outcome and better delivery of the products in recent time.